2011
DOI: 10.4067/s0717-92002011000300003
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation of basic wood density in Pinus ponderosa plus trees

Abstract: SUMMARYPhenotypic selection generally reduces the variability of both the selected trait and other associated characteristics. Some species show a negative strong relationship between growth traits and wood density. In the present study, basic wood density was assessed in a group of 23 control trees and 25 Pinus ponderosa plus trees, selected for growth and form traits in the Argentine Patagonia region. Trees were sampled in four different sites from the environmental and silvicultural point of view. We aim to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, in temperate region, wood density may vary considerably in the environment of an individual plant (increasing from the early to the late wood), but the variation between individuals of a given species remains limited and, more importantly, the mean wood density for a given species is generally highly conserved. Many studies have investigated the intraspecific variability of wood density, dissecting the phenotypic variation of wood density into genetic and environmental components (and their interaction) for most commercial forest tree species (Aguiar et al 2003;Bouffier et al 2008;Martinez-Meier et al 2011;Apiolaza 2011). The phenotypic coefficient of variation for wood density is generally low, as is the genetic additive coefficient of variation (these conclusions do not apply to interspecific crosses, such as Eucalyptus sp.)…”
Section: Introductionmentioning
confidence: 98%
“…However, in temperate region, wood density may vary considerably in the environment of an individual plant (increasing from the early to the late wood), but the variation between individuals of a given species remains limited and, more importantly, the mean wood density for a given species is generally highly conserved. Many studies have investigated the intraspecific variability of wood density, dissecting the phenotypic variation of wood density into genetic and environmental components (and their interaction) for most commercial forest tree species (Aguiar et al 2003;Bouffier et al 2008;Martinez-Meier et al 2011;Apiolaza 2011). The phenotypic coefficient of variation for wood density is generally low, as is the genetic additive coefficient of variation (these conclusions do not apply to interspecific crosses, such as Eucalyptus sp.)…”
Section: Introductionmentioning
confidence: 98%
“…Growth traits such as height and diameter can be used as criteria for getting superior genotypes. To date selection program to obtain superior genotypes has combined characteristics of growth with wood quality, such as moisture content, wood density and specific gravity (Gaspar et al 2009;Martinez-Meier 2011;Nocetti et al 2012;Muga et al 2014). Several studies have shown a significant correlation between growth and wood quality, such as in Gmelina arborea Roxb.…”
Section: Introductionmentioning
confidence: 99%